2018
DOI: 10.1016/j.ophtha.2017.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Endothelial Cell Loss in Patients with Artisan Myopia and Artisan Toric Phakic Intraocular Lenses

Abstract: A significant linear chronic EC loss was reported after implantation with myopic or toric iris-fixated pIOLs. A smaller ACD and smaller distance between pIOL edge and endothelium were risk factors for EC loss. Modification of preoperative age-related ECD thresholds is indicated to maintain an ECD that warrants safe future combined pIOL explantation and cataract surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
76
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 33 publications
6
76
1
5
Order By: Relevance
“…Doors et al [ 26 ] found that a shallow ACD and smaller distance between the pIOL edge and the endothelium were risk factors for ECD loss. In a recent study, Jonker et al [ 27 ] reported that in a group of 507 eyes, ECD had decreased by ≥25% in 7.9% of them, and ECD was <1500 cells/mm 2 in 3.9% at 10 years after implantation. Risk factors for increased ECD loss were a shallow ACD and a smaller distance between the central and peripheral pIOL edge to the endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Doors et al [ 26 ] found that a shallow ACD and smaller distance between the pIOL edge and the endothelium were risk factors for ECD loss. In a recent study, Jonker et al [ 27 ] reported that in a group of 507 eyes, ECD had decreased by ≥25% in 7.9% of them, and ECD was <1500 cells/mm 2 in 3.9% at 10 years after implantation. Risk factors for increased ECD loss were a shallow ACD and a smaller distance between the central and peripheral pIOL edge to the endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, detection of an acute loss early after the surgery and stabilization after the 3-month visit suggests that the main reason for the cell loss is surgical trauma and that the pIOL does not induce a clinically significant amount of ECD loss by itself, at least in the patients included in this study . Previous studies show that a smaller ACD is a significant risk factor for increased ECD loss in both anterior and posterior chamber pIOLs [ 11 , 25 ]. Accordingly, it is routine in our clinic to implant pIOLs of any type in only patients who have a ACD greater than 3.00 mm and the minimum anterior chamber depth (ACD) in this study was 3.04 mm from the endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Silva et al 12 reported a drop in the mean ECD of 14.05% at 5 years in 26 eyes. Jonker et al 13 implanted 127 eyes with the Artisan pIOL. The ECD showed a total loss of 16.6% over10 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%